UPAYA GURU PENDIDIKAN KEWARGANAGARAAN DALAM MENANAMKAN NILAI-NILAI KARAKTER RELIGIUS PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA TUNAS MUDA KECAMATAN SUNGAI RAYA KABUPATEN KUBURAYA - Octavia, Erna (Jurnal Pendidikan Kewarganegaraan, 2016)
Globalization has brought widespread impact in the outside world, not least in our country. The impact of globalization there is a positive, and the negative impact of which is violence, drug abuse, promiscuity and crime. All the negative things that led to the loss of the nations character. In addition, the character of the young generation is already at an alarming point. The morality of this nation has been separated from the norm, ethics, religion, and culture sublime, so sex becomes a phenomenon without being in the slightest weir. Sugeng (Asmani, 2011: 23) states that "lately the problem free sex (free sek) among young people are already very concerned, especially the youth and adolescents unfavorable level of planting their faith and piety". This is similar to what was stated by Asmani (2011: 24) the practice of premarital sex do students actually increased and almost equal in number between the city and in the regions. This happens due to the influence of western culture and the media through the shows that vulgar and likely to lead to pornography. The problems in the mentioned above are the challenges faced by educational institutions to improve the morality and character of students. School is an institution where students get an education and the teachers lessons. Schools prepare students to acquire knowledge, skills, character, increasing ketakwaaan to God Almighty to be able to equip themselves further towards higher education as a lifeline in the community.Â Keywords: efforts of teachers, instilling values of religious character, Citizenship Education.